Sleepless souls : suicide in early modern England / Michael MacDonald, Terence R. Murphy. - MacDonald, Michael, 1945- (Oxford studies in social history., 1990)
Suicide was regarded as a deplorable act, subject to savage punishments, in Tudor and Stuart England. In Georgian England it was de-criminalized, tolerated, and even sentimentalized. Drawing on a wide variety of contemporary sources, Sleepless Souls traces the causes of this dramatic shift in attitude. Michael MacDonald and Terence R. Murphy relate changes in opinion and practice to the complex framework of life in early modern England--including political events, religious changes, philosophical fashions, and differing class interests. Their analysis uncovers the forces that were reshaping the mental outlook of different English classes and social groups, and consequently provides an invaluable social and cultural history of English society over three centuries.